Influences on Bereaved Family Uptake of Chaplaincy Support when Viewing the Deceased Person: A Case Series Study in Controlled Conditions - Kevern, Peter; Walker, Wendy; Jones, Jennifer; Owen, Stacey; Efstathiou, Nikolaos (Health and Social Care Chaplaincy, 2025)
It is a belief widely held that hospital chaplains have a role to play in supporting bereaved relatives of patients, but research on the subject is sparse. The aim of this study was to examine factors that apparently influenced the decision to accept or refuse the offer of chaplaincy support through a case series study of ten bereaved family members who accessed an in-hospital “supported viewing service” following the sudden or unexpected death from natural causes of an adult relative. Data gathered at a UK hospital between October 2022 and April 2023 were subjected to qualitative content analysis. Analysis of the interview data yielded four categories that governed the decision: (1) Who decides? (2) Who benefits? (3) Role of religious preference and context. (4) Positive reasons for rejection. These indicate that the response to the offer of prayer is contingent on details of the biographical, temporal, social and religious context which need to be considered when the offer is made.